PANDANGAN GEREJA KATOLIK TERHADAP BÖWÖ DALAM TRADISI PERKAWINAN SUKU NIAS - Febri Ompu Sunggu; Agusman Giawa; Yohanes Endi (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2023)
This reaserch discusses the meaning of böwö or dowry in traditional Nias marriage and the Catholic Church's view. In general, böwö has a high meaning of respect for a marriage and for the family that has cared for the child. However, today the author sees that the tradition of giving böwö or dowry no longer prioritizes the original meaning of the böwö. My hypothesis is that the original meaning of the dowry or böwö in traditional Nias marriages has lost its meaning. The dowry or böwö is limited to showing one's status. Someone who can provide a large dowry or böwö is considered a mature person and automatically has a place in social life. However, for those who are unable to pay off the dowry or böwö that has been determined, they will have to pay over a long period of time, which will affect the welfare of the family. The meaning of dowry or böwö was first in line with the Catholic Church, but nowadays it is completely contradictory. Catholic marriage emphasizes the well-being of the family, but a high böwö can be a burden. In accordance with the Catholic Church's view, the author finds that today the fulfilment of böwö is facultative, as böwö is not the determinant of whether a marriage is valid or not. Family welfare is paramount in Catholic marriages.